Acute Static Stretching Reduces Lower Extremity Power in Trained Children - McNeal, J. R.; Sands, W. A. (Pediatric Exercise Science, 2003)
Several studies utilizing adult subjects have indicated that static stretching may reduce subsequent strength and power production, possibly for as long as an hour following the stretch. This observation has not been evaluated in children, nor in athletes accustomed to performing static stretches during strength/ power type training sessions. The purpose of this investigation was to determine if an acute bout of passive, static stretching of the lower extremity would affect jumping performance in a group of young, female gymnasts. Thirteen competitive gymnasts (age 13.3 ± 2.6 yrs) performed drop jumps under two conditions: immediately following stretching and without prior stretching. The jumps were performed on separate days. The conditions were randomly ordered among the subjects. Time in the air (AIR) and ground contact time (CT) were measured during the drop jumps using a timing mat. Three different stretches of the lower extremity were conducted on each gymnast twice, each stretch being held for 30 seconds. Following the stretching condition, AIR was significantly reduced (.44 vs .46 sec, p < .001), while CT was not different (.130 for both conditions, p > .05). This study demonstrates that children`s lower extremity power is reduced when the performance immediately follows passive, static stretching, even in children accustomed to static stretching during training sessions involving explosive power.